Powered Endoscopic Dacryocystorhinostomy. Issue 3 (May 2015) - Ali, Mohammad Javed; Psaltis, Alkis James; Murphy, Jae; Wormald, Peter John
<x xml:space="preserve">Abstract</x> Purpose: To report a decade long experience with powered endoscopic dacryocystorhinostomy (DCR). Methods: A retrospective review of all consecutive patients undergoing powered endoscopic DCR was performed at this institution over a period of 11 years from 2002 to 2013. All patients completed a minimum of 3 months follow up following stent removal. Patient records were reviewed for demographic data, clinical and surgical profiles, adjunctive procedures, complications, and success rates at the last follow up. Anatomical success was defined as patent ostium on irrigation and functional success as free flow of dye into ostium on functional endoscopic dye test and resolution of epiphora. Results: Two hundred eighty-three powered endoscopic DCRs were performed on 214 patients. The mean age at surgery was 59.5 years (range, 3–95 years). All patients presented with epiphora. A total of 91.6% patients (196/214) had a primary DCR and 8.4% (18/214) had a revision DCR. In all, 50.4% patients (108/214) underwent adjunctive endonasal procedures. The mean follow up was 17.1 months (range, 3–103 months). At the last follow up, the final anatomical success was achieved in 96.9% cases of primary DCRs and 91.3% cases of revision DCRs. Functional success was achieved in 93% cases of primary DCRs and 86.9% cases of revision DCRs. Conclusions: Powered endoscopic DCR is a safe procedure and offers excellent results both in primary and revision DCRs. The threshold to perform adjunctive endonasal procedures should be very low when indicated.